Influence of economic growth and energy consumption on carbon emissions in Yangtze River Economic Belt. Issue 1 (November 2020) - Han, Yuling; Liu, Yiping
Abstract: This paper investigated the influence of economic growth and energy consumption on carbon emissions by using an extended STIRPAT model with panel data in Yangtze River Economic Belt from 2000 to 2017. We applied PCA to avoid the multicollinearity of the variable. The results show that the per capita GDP, the industrial structure, the population scale, the population structure, the export scale, the investment scale, the consumption and the FDI all lead to the increase of carbon emissions. The energy intensity has an inhibitory effect on carbon emissions. The EKC hypothesis is confirmed in Yangtze River Economic Belt, but in the west part, the economic growth and carbon emissions exhibit a reversed N-shaped relationship. The three control variables which promote economic growth, respectively, the export scale has the strongest effect in promoting the carbon emissions in the whole area, the investment scale has the biggest influence in the east part, the consumption has the largest impact in the mid-west part. Finally, some suggestions are provided.